Proximate Composition, Minerals, Heavy Metal And Pesticide Resudues esticide Resudues Of Three Popular Cut-Up Parts Of Commercial Chicken From North 24-Parganas Area, West Bengal est Bengal - Chakraborty, A.; Biswas, S.; Chakraborty, R.; Majumder , D.; Majumder, D.; Chakraborty, A. Dhargupta (Journal of Meat Science, 2014)
Study was conducted to determine the proximate and mineral composition as well as heavy metals and pesticide residues in three popular cut-up parts (drumstick, breast and wing) of commercial chicken. A total number of 120 broiler birds of 35-42 days of age were selected from different areas of North 24-Parganas, West Bengal and the slaughtering and dressing were done as per the standard procedure. The data were analyzed statistically for valued conclusion. Significant (P
Keywords: proximate composition; mineral; heavy metal; cut-up parts; chicken